PEMBENTUKAN KATA PADA LIRIK LAGU EBIET G. ADE - Wiryananda, Ni Made Suryaningsih (Humanis, 2016)
This study is aimed to analyze and to understand the process of formulating words pharases in songs created by Ebiet G. Ade. The object of the study are phrases taken from Camellia album 1-4 by Ebiet G. Ade ,therefore data sources of the study are phrases from the above- mention songs compalition. Structural morphology theory is utilised in the study. Data analyze based on the formulation of phares as well as typical words formulation.
Keywords: words phrases, Ebiet G. Ade, song lyric, typical words formulation